2022
DOI: 10.1186/s40662-022-00285-3
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of myopic maculopathy from color fundus photographs using deep convolutional neural networks

Abstract: Background Myopic maculopathy (MM) has become a major cause of visual impairment and blindness worldwide, especially in East Asian countries. Deep learning approaches such as deep convolutional neural networks (DCNN) have been successfully applied to identify some common retinal diseases and show great potential for the intelligent analysis of MM. This study aimed to build a reliable approach for automated detection of MM from retinal fundus images using DCNN models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The results showed that the detection accuracy of this auxiliary classification system for all lesions except choroidal neovascularization was more than 84%, and the overall detection accuracy for myopic macular degeneration was up to 87.53%, whereas the classification accuracy of ophthalmology specialists on the same task was merely 89%. A study by Li et al (2022c) showed similar results, further confirming the effectiveness of EfficientNet. However, according to Du et al (2021) , the detection of choroidal neovascularization was only 37.07%, which might be related to the poor visualization of blood vessels in color fundus images ( Jiang et al, 2020 ; Laíns et al, 2021 ).…”
Section: Ai Technology For Myopia Screening and Diagnosissupporting
confidence: 62%
“…The results showed that the detection accuracy of this auxiliary classification system for all lesions except choroidal neovascularization was more than 84%, and the overall detection accuracy for myopic macular degeneration was up to 87.53%, whereas the classification accuracy of ophthalmology specialists on the same task was merely 89%. A study by Li et al (2022c) showed similar results, further confirming the effectiveness of EfficientNet. However, according to Du et al (2021) , the detection of choroidal neovascularization was only 37.07%, which might be related to the poor visualization of blood vessels in color fundus images ( Jiang et al, 2020 ; Laíns et al, 2021 ).…”
Section: Ai Technology For Myopia Screening and Diagnosissupporting
confidence: 62%
“…Figure 1 shows the flowchart of the literature eligibility process. Finally, 22 studies were included for systematic review [ 12 33 ], and 14 of them were included for quantitative meta-analysis [ 12 , 13 , 16 , 19 23 , 26 , 27 , 29 – 31 , 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers had also done research on multiple macular disorders. Li et al (2022) used DCNN-DS model to detect no myopic maculopathy, tessellated fundus, and pathologic myopia, and the validation accuracies on the two external testing datasets were 96.3 and 93.0%, respectively. Tang et al (2022) used ResNet-50 model to develop the META-PM study categorizing system, and the mean accuracy was 0.9119 ± 0.0093 on the five categories.…”
Section: Discussionmentioning
confidence: 99%